A microsystem integrating photodegradable hydrogel microstructures and reconfigurable microfluidics for single-cell analysis and retrieval. Issue 3 (25th November 2014) - Son, Kyung Jin; Shin, Dong-Sik; Kwa, Timothy; You, Jungmok; Gao, Yandong; Revzin, Alexander
Abstract : We developed a micropatterned photodegradable hydrogel array integrated with reconfigurable microfluidics to enable cell secretion analysis and cell retrieval at the single-cell level. Abstract : We developed a micropatterned photodegradable hydrogel array integrated with reconfigurable microfluidics to enable cell secretion analysis and cell retrieval at the single-cell level. The activity of protease molecules secreted from single cells was monitored using FRET peptides entrapped inside microfabricated compartments. Antibody-modified gel islands tethering cells to the surface could be degraded by UV exposure to release specific single cells of interest.